The health of US adolescent athletes during Covid-19 related school closures and sport cancellations - McGuine, T. A.; Biese, K. M.; Petrovska, L.; Hetzel, S. J.; Reardon, C.; Kliethermes, S.; Bell, D. R.; Brooks, A.; Watson, A. M. (Journal of Athletic Training, 2020)
Context: In the spring of 2020, US schools closed to in-person teaching and sports were cancelled to control the transmission of COVID-19. It is critical to understand the mental and physical health of adolescent athletes during this time.